HUBUNGAN ANTARA KETELADANAN ARANG TUA DENGAN KECERDASAN MORAL ANAK PAUD ASHHABUL KAHFI CENDANA MATA AIR KECAMATAN PADANGSELATAN KOTA PADANG - Inawati dan MHD Natsir (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2014)
The problem in this study is the low exemplary parents in early childhood education with moral intelligence in PAUD Ashhabul Kahfi.. The purpose of this study in order to illustrate exemplary parents, describe exemplary moral intelligence of children and parents in PAUD Ashhabul Kahfi Cendana Mata Air Kecamatan Padang Selatan Kota Padang. By using the descriptive research methodology. The population in this study is local parents B1 and B2 which totaled 50 people. The samples in this study were randomly drawn as many as 30 people. echnique data collecting data using questionnaires and data analysis techniques using quantitative descriptive techniques with percentage calculations. The results showed that the exemplary parents still low, the moral intelligence of children are still low and there is a significant relationship between parents' example with moral intelligence of children in PAUD Ashhabul Kahfi Cendana Mata Air Kecamatan Padang Selatan Kota Padang